Odpowiedzi

2010-02-01T16:17:38+01:00
C) -16x+2x^2-5x^2-15x=-3x^2-31x
d) 15-10x-12x-18=-22x-3
e) -x+5-4=-x+1
f) 2x+4+3=2x+7
g) -2x-2x-12=-4x-12
h) 2(x-1)-30x-10=2x-2-30x-10=-28x-12
12 3 12
2010-02-01T16:21:00+01:00
3:zapisz w jak najprostszej postaci

c)-2x(8-x)-5(x do kwadratu +3x)=-16x+2x²-5x²-15x

d)5(3-2x)-(4x+6)*3=15-10x-12x+18

e)2x+5-3x-12:3=-1x+1

f)12x+16:4-10x+15:5=2x+7

g)9-6x:3-21-14x:7= 9-2x -21 -2x= 12-4x

h)4(x-1):2-3*10x-50:5 =2:(4x-4 )-30x- 10 =2x-2-30x -10= -28x-12
7 4 7
  • Użytkownik Zadane
2010-02-01T16:21:40+01:00
C)-2x(8-x)-5(x² +3x)=-16x-2x²-5x²-15x=-16x-15x-2x²-5x²=-31x-7x²
d)5(3-2x)-(4x+6)×3=15-10x-4x+6×3=15+18-10x-4x=33-14x
e)2x+5-3x-12:3=2x-3x+5-4=-x+1
f)12x+16:4-10x+15:5=12x-10x+4+5=-2x+9
g)9-6x:3-21-14x:7=9:3-21:7-14x-6x=-20x
h)4(x-1):2-3×10x-50:5=4x-4:2-3×10x-50:5=4x×10x-3-4:2-50:5=40x-3-2-10=40x-15
6 2 6